COMPLICATIONS OF MECHANICAL VENTILATION IN CHILDREN UP TO 12 Y OF AGE - SHARMA, VIJAY LAXMI; PHIRKE, DEEPA; KHALATE, SHRADDHA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Mechanical ventilation has been proven to be lifesaving and has significantly reduced mortality in the pediatric population. Despite its life-saving advantages, mechanical ventilation is associated with complications. The study aimed to assess the complications of mechanical ventilation in children up to 12 y of age admitted to the intensive care unit. Methods: The present descriptive, observational, cross-sectional study was conducted on 165 children aged between 0 to 12 y, who were mechanically ventilated for>48 h. Patients were observed daily until the desired result was achieved and were checked to look for complications or negative effects of mechanical ventilation. Results: The majority of subjects belonged to<1 mo of age (77.58%) whereas the maximum number of patients were male (64.24%). In 77.58% of patients, the indication for mechanical ventilation was respiratory failure. The duration of ventilation in 62.43% of patients was>7 d. A total of n=62 (37.58%) patients had ventilator-associated complications. The most common complication was ventilator-associated pneumonia (n=30, 48.38%). The mean hospital stay was found to be 22.88±7.96 d. Whereas the mean hospital stay in patients without complications was significantly less compared to patients with complications (18.57±10.09 d vs 27.19±5.83 d, P=0.00015). The mortality rate was found to be 47.27%. Conclusion: Respiratory cause was the most common indication for mechanical ventilation. The most common complication was ventilator-associated pneumonia. The subjects with complications had prolonged hospital stays.